Comparison the Effect of Eight Weeks Pyramid Resistance Training With two Patterns on Bio-motor Ability and Anthropometrical in Wrestlers - Ghadir Ali Omidbakhsh; Mehrdad Fathi; Keyvan Hejazi (Islamic Azad University, Hamedan Branch, 2020)
Objective: Wrestling is a fast-paced activity in which resistance training is essential to improve athlete performance. We evaluated the effect of comparison of the effect of eight weeks resistance training with two patterns of pyramidal and inverse pyramidal on bio-motor ability, Anthropometrical and skill profile of freestyle wrestlers. Methods: In this semi experimental study, 24 male freestyle wrestlers were randomly assigned into two groups [pyramidal (n=12) and inverse pyramidal endurance (n=12)]. The pyramidal and inverse pyramidal resistance training included (8 weeks, 3 times per a week, 60 minutes per session). Bio-motor ability, Anthropometrical and skill profile were measured at baseline and at the end of the study. Paired and independent sample t-test were used to compare within and between-group means and the results were tested at the significant level P<0.05. Results: Training lead to changes on weight, body mass index, body fat percent, maximum power into pyramidal and inverse pyramidal groups (P<0.05). Anaerobic power, explosive power, muscular endurance increased significantly in both pyramidal and inverse pyramidal patterns. There were significant differences in the between-group mean changes in the variables of weight, body mass index and muscular endurance between the two experimental groups (P<0.05). Conclusion: Resistance exercises with pyramidal and inverse pyramidal patterns led to significant weight loss, body mass index, body fat percentage, and improvement of skill profile and biometric indicators. Therefore, using both types of training may have a positive effect on wrestlerschr('39') performance indicators.